UPAYA PERLINDUNGAN HAK ASASI PEREMPUAN SEBAGAI KORBAN KEKERASAN DI SUMATERA UTARA - Junaidi; Hodriani (STIH Zainul Hasan Kraksaan Kraksaan, 2024)
Protection, fulfillment, and respect for women's human rights are the responsibility of various parties, both state institutions and community institutions and even political parties. However, there are still many acts of violence against women. The purpose of this research is to find out how to protect women's human rights as victims of violence in North Sumatra. The research method used in this study is the literature literacy method with data collection instruments in the form of books, journals, websites and other sources. The data analysis technique used is the Miles and Huberman model, namely data reduction, data display, and verification. The results of the study are that there are still many cases of violence against women that occur in Indonesia with a total of 2,389 cases in 2020 and in North Sumatra in particular as many as 35 cases of violence against women. efforts to protect against violence the government of North Sumatra has established a Regional Regulation and the Governor of North Sumatra established the Minimum Service Standard for Integrated Services, and Regional Regulation number 3 of 2019 concerning the Protection of Women and Children from Violence.